Impact of vaccination on kinetics of neutralizing antibodies against SARS-CoV-2 by serum live neutralization test based on a prospective cohort - Liguo Zhu; Naiying Mao; Changhua Yi; Aidibai Simayi; Jialu Feng; Yi Feng; Min He; Songning Ding; Yin Wang; Yan Wang; Mingwei Wei; Jie Hong; et al. (Emerging Microbes and Infections)
How much the vaccine contributes to the induction and development of neutralizing antibodies (NAbs) of breakthrough cases relative to those unvaccinated-infected cases is not fully understood. We conducted a prospective cohort study and collected serum samples from 576 individuals who were diagnosed with SARS-CoV-2 Delta strain infection, including 245 breakthrough cases and 331 unvaccinated-infected cases. NAbs were analysed by live virus microneutralization test and transformation of NAb titre. NAbs titres against SARS-CoV-2 ancestral and Delta variant in breakthrough cases were 7.8-fold and 4.0-fold higher than in unvaccinated-infected cases, respectively. NAbs titres in breakthrough cases peaked at the second week after onset/infection. However, the NAbs titres in the unvaccinated-infected cases reached their highest levels during the third week. Compared to those with higher levels of NAbs, those with lower levels of NAbs had no difference in viral clearance duration time (P>0.05), did exhibit higher viral load at the beginning of infection/maximum viral load of infection. NAb levels were statistically higher in the moderate cases than in the mild cases (P<0.0001). Notably, in breakthrough cases, NAb levels were highest longer than 4 months after vaccination (Delta strain: 53,118.2 U/mL), and lowest in breakthrough cases shorter than 1 month (Delta strain: 7551.2 U/mL). Cross-neutralization against the ancestral strain and the current circulating isolate (Omicron BA.5) was significantly lower than against the Delta variant in both breakthrough cases and unvaccinated-infected cases. Our study demonstrated that vaccination could induce immune responses more rapidly and greater which could be effective in controlling SARS-CoV-2.